(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This article discusses the impact of harmful substances on human health in the production of building materials and measures to prevent negative consequences. And also, information about the health of the population of the Samarkand region. And also, this article describes the preparation of initial data for the calculation of surface concentrations of pollutants, the use of inventory materials. Calculation of the dispersion of pollutants into the atmosphere according to universal programs. And also, the rules for the field of dispersion of pollutants in the surface layer of the atmosphere are given.